Preservation of Traditional Art in the Modern Era: A Case Study of Seudati Dance in the Disruption Era in Pidie Jaya Regency - Mujiburrahman, Mujiburrahman; Meliza, Richa; Riski, Aflia; Yunanda, Rizki; Kamil, Ade Ihsan; Chalid, Ibrahim; Rahmatika, Assyfa; Nizar, Raudatun (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Andalas, 2024)
The focus of this research is on the strategies for preserving Seudati dance by the Pidie Jaya government in the era of disruption. Pidie Jaya is one of the regencies known for the Seudati dance, and many prominent Seudati leaders, known as